Programmable chips for 5G applications: The new generation of green and smart hardware for 5G. Issue 1 (12th January 2022) - Gonzalez, Ana; Costa, Diogo
Abstract: 5G deployment is facing significant challenges with the need for novel technologies able to increase data density in current networks. These include antennas and radio access network (RAN) hardware, which are driven by the growing bandwidth requirements in access networks.